ANALISIS YURIDIS TERHADAP UPAYA HUKUM LUAR BIASA PENINJAUAN KEMBALI DALAM SISTEM HUKUM ACARA PIDANA - Yadnya, Putu Andhika Kusuma; Pradana, I Gede Made Oka Putra (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
This study delves into the process and implications of the legal remedy of "Peninjauan Kembali" (Reconsideration) within the Criminal Procedure Law in Indonesia. It examines the formal and substantive criteria for submitting a reconsideration request, using the case of Irman Gusman as a prominent example. Employing a normative approach and drawing on primary and secondary legal sources, the research meticulously analyzes the procedural steps involved in submitting a reconsideration request. Special emphasis is placed on the formal prerequisites that must be met and the material grounds that warrant such an action. By shedding light on the intricacies of the reconsideration process, this study contributes to a deeper understanding of how this legal remedy operates within the criminal justice system. Furthermore, it elucidates the potential legal consequences that arise if a reconsideration request proves successful, leading to modified judgments that can significantly impact the existing legal framework. The insights provided in this research have implications not only for legal practitioners and scholars but also for individuals seeking a comprehensive grasp of the Indonesian criminal justice system's intricacies.